The Influence of Emotional Intelligence and Self-Acceptance on Resilience in Students Who Have Broken Up in Love at Muhammadiyah University of Sidoarjo : Pengaruh Kecerdasan Emosi dan Penerimaan Diri Terhadap Resiliensi Pada Mahasiswa Yang Pernah Mengalami Putus Cinta di Universitas Muhammadiyah Sidoarjo - viki vinda kurniawati_; Lely Ika Mariyati (Academia Open, 2025)
General Background: Early adulthood is a developmental phase marked by emotional challenges, particularly following romantic relationship dissolution. Specific Background: Difficulties in emotion regulation and self-acceptance often hinder psychological recovery during this period. Knowledge Gap: Previous studies largely examined resilience independently, leaving limited evidence on its simultaneous association with emotional intelligence and self-acceptance among early adults experiencing breakup. Aims: This study aims to examine the relationships between emotional intelligence, self-acceptance, and resilience in early adulthood after breakup experiences. Results: Findings indicate significant positive associations among emotional intelligence, self-acceptance, and resilience, suggesting that individuals with stronger emotional regulation and higher self-acceptance demonstrate greater adaptive capacity. Novelty: This study integrates emotional intelligence and self-acceptance within a unified resilience framework among early adults post-breakup, providing empirical evidence in an underexplored context. Implications: The results highlight the importance of psychosocial interventions focusing on emotional regulation and self-acceptance to support resilience development in young adults. These findings offer practical relevance for counseling services and mental health programs in higher education settings. Keywords: Resilience, Emotional Intelligence, Self Acceptance, Early Adulthood, Breakup Experience Key Findings Highlights: Emotional intelligence shows a strong association with adaptive coping capacity. Self acceptance contributes meaningfully to psychological recovery. Integrated personal resources support adjustment after relationship loss.